2017
DOI: 10.1016/j.neuropsychologia.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness increases after simultaneous interpretation training

Abstract: Simultaneous interpretation is a complex cognitive task that not only demands multilingual language processing, but also requires application of extreme levels of domain-general cognitive control. We used MRI to longitudinally measure cortical thickness in simultaneous interpretation trainees before and after a Master's program in conference interpreting. We compared them to multilingual control participants scanned at the same interval of time. Increases in cortical thickness were specific to trainee interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 70 publications
(105 reference statements)
3
58
0
Order By: Relevance
“…First, a study on executive functions (including STM and updating tasks) revealed no differences between UMs and aspiring interpreters about to start their training (Rosiers, Woumans, Duyck & Eyckmans, 2019). Second, as seen above, longitudinal research comparing ISs before and after periods of intensive practice (and UMs at the same time points) has shown increased performance for the trainees in key SI-related functions, such as WM (Antonova Ünlü & Sağın Şimşek, 2018), in addition to structural (Hervais-Adelman et al, 2017) and functional (Hervais-Adelman et al, 2015) brain changes in critical hubs. Complementarily, various neurocognitive effects in PSIs are significantly associated with their hours of practice (Elmer, Hänggi & Jäncke, 2014) and their years of professional experience (Santilli et al, 2018), indicating that the longer the experience in SI, the greater its effects on particular cognitive systems.…”
Section: Discussion: On the Adaptability Of Neurocognitive Systems Inmentioning
confidence: 93%
“…First, a study on executive functions (including STM and updating tasks) revealed no differences between UMs and aspiring interpreters about to start their training (Rosiers, Woumans, Duyck & Eyckmans, 2019). Second, as seen above, longitudinal research comparing ISs before and after periods of intensive practice (and UMs at the same time points) has shown increased performance for the trainees in key SI-related functions, such as WM (Antonova Ünlü & Sağın Şimşek, 2018), in addition to structural (Hervais-Adelman et al, 2017) and functional (Hervais-Adelman et al, 2015) brain changes in critical hubs. Complementarily, various neurocognitive effects in PSIs are significantly associated with their hours of practice (Elmer, Hänggi & Jäncke, 2014) and their years of professional experience (Santilli et al, 2018), indicating that the longer the experience in SI, the greater its effects on particular cognitive systems.…”
Section: Discussion: On the Adaptability Of Neurocognitive Systems Inmentioning
confidence: 93%
“…Grey matter volumetric changes have been reported in the inferior parietal lobules (IPL) (e.g., left IPL: Mechelli et al, 2004;bilateral IPLs: Abutalebi et al, 2015b), left inferior frontal cortex (IFC) (e.g., Klein et al, 2014), the anterior cingulate cortex (ACC) (e.g., Abutalebi et al, 2012;2015a) and basal ganglia (e.g., left Putamen: Abutalebi et al, 2013b;left Caudate: Zou et al, 2012). These BLC regions have also been reported as the loci of grey matter-related increases in studies of adult second language learning (e.g., left IFC & IPL: Legault et al, 2018;left IFC: Stein et al, 2010), and in studies involving specialized linguistic training, such as simultaneous interpretation (SI) (e.g., right IPL: Hervais-Adelman et al, 2017;left IFC: Martensson et al, 2012). These findings are not surprising.…”
Section: Introductionmentioning
confidence: 92%
“…Sixty-seven of the datasets were acquired as part of a separate study (Hervais-Adelman et al 2017), in which no analyses of the relationship between subcortical morphology and LEXP were carried out. 1 Of the 75 participants 40 had a acquired at least 1 s language before 6 years of age, and may be considered "early bilinguals", and 35 only began acquiring their second and further languages after this age, and may be considered "late bilinguals"; these groups did not differ in terms of LEXP (overall: t (69.13) = 0.385, p = 0.70, proficiency only: t (68.87) = 1.34, p = 0.19) or age (t (66.99) = 1.03, p = 0.31).…”
Section: Participants and Behavioural Measuresmentioning
confidence: 99%
“…Nevertheless, we are minded to agree with Bialystok (2017) that it could be considered disingenuous to posit that the experience of multilingualism should have no effect on the brain at all. Indeed, there is substantial evidence, also from longitudinal studies, that bilingualism and language training influence brain function (Becker et al 2016;Costumero et al 2015), and also brain structure (Hervais-Adelman et al 2017;Stein et al 2012). These findings are consistent with the notion that learning can indeed change the brain, even structurally, at micro-and macro-structural scales (Zatorre et al 2012).…”
Section: Introductionmentioning
confidence: 99%